Importance of nursing care in the prevention of unplanned teenage pregnancy: a narrative review of the literature (Research, Society and Development, 2022)
Adolescence presents itself as a challenge for health professionals, as it is a phase characterized by constant discoveries and changes in physical, mental and psychological development. In this sense, the objective of this study was to know the actions of the nursing team towards adolescents aiming to reduce the rates of unplanned pregnancy. The present study is a literature review of the narrative type. To obtain the data, searches were carried out in the following databases: LILACS, SCIELO and MEDLINE, using the following health descriptors (DECS): Adolescent; Nursing; unplanned pregnancy; Health education. The articles showed that nursing work is fundamental in reducing the number of cases of teenage pregnancy. To this end, nurses can develop educational practices that involve, from conversations to groups of adolescents, as well as partnerships with schools, communities and counseling. Merging group and individual educational practices are key strategies as they favor integration and help adolescents in their difficulties. Stimulating the exchange of experiences, considering that they share the same anxieties and questions. The relevance of education and health interactions is also highlighted, with the objective of finding new ways and actions to engage, guide and respond to the adolescent public, in order to reduce unplanned pregnancy rates.